New configurable low-cost solar roofs: developing a new paradigm for more sustainable houses - Juanico, Luis Eduardo (2012)
A new design of roof-integrated water solar collector is presented. It takes advantage of new synergies found between collector and roof. Its main concept is based on the use of water redistribution for changing the roof configuration. This system is completely suitable for inclined roofs, since it is based on waterproofed plastic chambers. This design provides a universal low-cost system for household heating and natural cooling that could be even cheaper than conventional roofs with similar (high) thermal qualities. This novel design has been claimed in an Argentinean invention patent application and also it has been internationally claimed.